Risk of cache pilferage determines hoarding behavior of rodents and seed fate. (4th April 2018) - Cao, Lin; Wang, Bo; Yan, Chuan; Wang, Zhenyu; Zhang, Hongmao; Geng, Yuanzhao; Chen, Jin; Zhang, Zhibin
Abstract : Rodents adjust predation and hoarding behavior according to the probability of their hoarding seeds being stolen by competitors. Rodents eat unsafe seeds (seeds more likely to be stolen) immediately and keep safe seeds (seeds less likely to be stolen) for a long time. Rodents spread their seeds in many small "storehouses" when the probability of hoarded seeds being stolen is high and hoard many seeds in one "storehouse" when the probability is low. Abstract: Cache pilferage by competitors is thought to drive the evolution of hoarding behavior in animals, which plays significant roles in tree regeneration and formation of mutualisms between trees and animals. However, little is known how cache pilferage risk among seeds of different tree species or years affects hoarding behavior and seed dispersal by animals. We hypothesized that scatter-hoarding rodents could adjust hoarding behavior according to variation in cache pilferage risk among seeds and years to minimize cache pilferage, by investigating the relationship between cache pilferage risk and seed dispersal of 7 tree species over 3 years in tropical forest in southwest China. Among years, the high pilferage risk was related to high probability of larder-hoarding and short periods of scatter-hoarding; whereas, the probability of scatter-hoarding was higher in intermediate pilferage year than in both low and high pilferage years. Among seeds, high pilferage risk was related to low probability and short periods of scatter-hoarding. Our results indicated that cache pilferage risk significantly affected hoarding behaviors and seed dispersal by scatter-hoarding rodents as well as seed fates. Cache pilferage risk was a reliable explanatory factor for variation in seed dispersal, and it might be an important driving force in the evolution of rodent hoarding behaviors and seed characteristics.